PENGARUH PERTUMBUHAN PENJUALAN, TOTAL ASSET TURNOVER, MODAL KERJA, DAN STRUKTUR MODAL TERHADAP PROFITABILITAS DAN UKURAN PERUSAHAAN SEBAGAI VARIABEL KONTROL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2015 – 2017 - Arin Affifah, 15.05.52.0258; Lisiantara, G. Anggana (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the effect of sales growth, total asset turnover, working capital, and capital structure on profitability and firm size as a control variable in manufacturing companies listed on the Indonesia Stock Exchange in the period 2015-2017. The population in this study are all Manufacturing Companies Registered on the Stock Exchange of the 2015-2017 Period. The sample selection uses a purposive sampling method. The analytical tool used in this study is multiple linear regression analysis. The test results show that partially sales growth does not affect profitability, total asset turnover, working capital, and firm size have a significant positive effect on profitability. While the capital structure has a significant negative effect on profitability.